SISTEM PEMANTAUAN KUALITAS UDARA MENGGUNAKAN CLOUD APPLICATION BLUEMIX - Sarosa Castrena Abadi (Jurnal Elektra, 2019)
Air pollution monitoring is a method used to determine air quality at particular location. The air quality assessment system through internet provides realtime air quality information. The objective of the use of microcontroller and sensors on the system is to measure levels of contaminants in the air. So it is able to provide information about air quality at a point in the area as well as the harmful content in it. In this design, a Bluemix cloud service from IBM was also implemented to provide data access for users anywhere and anytime using a browser or Android- based application.